Characterizing the exposure-response relationship of idecabtagene vicleucel in patients with relapsed/refractory multiple myeloma - Jamie N. Connarn; Han Witjes; Marielle van Zutphen‐van Geffen; Rik deGreef; Timothy B. Campbell; Kristen Hege; Simon Zhou; Manisha Lamba (Wiley, 2023)
Abstract Idecabtagene vicleucel (ide‐cel; bb2121) is a B‐cell maturation antigen-directed chimeric antigen receptor (CAR) T cell therapy approved for treatment of patients with heavily pretreated relapsed and refractory multiple myeloma. This analysis evaluated exposure-response (ER) relationships of ide‐cel with key efficacy end points and safety events. Ide‐cel exposure data were available from 127 patients treated at target doses of 150, 300, or 450 × 106 CAR+ T cells from the phase II KarMMa study (NCT03361748). Key exposure metrics, including area under the curve of the transgene level from 0 to 28 days and maximum transgene level, were calculated using noncompartmental methods. Logistic regression models, using both linear and maximum response function of exposure on the logit scale, were evaluated to quantify observed ER trends, and modified by including statistically significant individual covariates in a stepwise regression analysis. There was wide overlap of exposures across the target doses. ER relationships were observed for the overall and complete response rates, with higher response rates associated with higher exposures. Model‐based evaluations identified female sex and baseline serum monoclonal protein less than or equal to 10 g/L as predictive of a higher objective response rate and a higher complete response rate, respectively. ER relationships were observed for safety events of cytokine release syndrome requiring tocilizumab or corticosteroids. The established ER models were used to quantify the ide‐cel dose-response, which showed a positive benefit-risk assessment for the range of ide‐cel exposures associated with the target dose range of 150-450 × 106 CAR+ T cells.